Relationship of economic development stages and human life conditions quality of life as a modern one-off-a kind result of the historical evolution of humanity - Kim M. М. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The article focuses on the relationship between the stages of economic development of the society and the condition of human life. The leading role of the quality of life amidst related and adjoined concepts such as the way and standard of living, its well-being and others was determined. The quality of life as a phenomenon and as a category was considered and also how the concept of quality of life goes through the stages of origin, formation, development and maturity. The instrumental definition of the quality of life as the sum total of objective conditions of people’s and social groups’ lives as well as their subjective assessments and feelings was substantiated. The article examines the impact of economic development degree on subjective well-being and happiness as a component of the quality of life. The author gives a preliminary conclusion that the higher the level of economic development, the weaker its impact on the level of happiness of the population, but in poor countries, the main factor of subjective well-being and happiness is material well-being. In any case, for happiness, one should have the minimum required level of material well-being. The article devoted a considerable attention to the relationship between the stages of economic development and the conditions of human life. Domestication of wild animals and plants puts the onset of human life, the agrarian stage marked the proto well-being that turns into well-being. The industrial age of production provided for a high standard of living, and the post-industrial stage – for a quality of life. The latter is a one-off-a kind result of the historical evolution of the humanity. The need for pressing tasks to stop the fall and stabilize and raise the level and quality of life in the present-day Ukraine was justified. Judging by their structure in our country, accelerated economic growth and GDP growth in general and per capita is number one priority. It is necessary to carry out re-industrialization on the basis of modernization by implementing the new industrial policy announced by the Government of Ukraine.